Hedge com diversificação de atividades agropecuárias - Xavier, Karine Diniz (2013)
This study presents an instrument for farmers and general users to mitigate the risk on the agricultural market. Such instrument refers to different portfolios from a table composed of several agricultural activities. These portfolios are accompanied by its risk and monthly operating payback, along with optimal allocation of its financial resources and the area of rural property for each activity. Whence, eight agricultural activities economically relevant to the State of Goiás were primarily selected (cotton, rice, beef cattle, bean, corn, soybean, sorghum and tomato) and the monthly medium prices series received by farmers were researched at the Companhia Nacional de Abastecimento – Conab. Also, the series of operational costs per hectare were collected from the Federação da Agricultura e Pecuária de Goiás – Faeg. Posteriorly, the operating payback of each related activity was calculated and checked the stationarity of the payback series. After confirmed the stationarity of the time series, the volatility of the payback series from each activity was analyzed. Then was calculated the matrix of correlation between the activities payback on the study and the model of linear programming, which has the equation proposed by Markowitz (1952) as objective function in order to minimize the portfolio risk. The results show portfolios with combinations of two, three, four, five and six agricultural activities. It was possible to check that Portfolio 1, composed by corn and soybean activities, showed greater level of monthly operational payback, 15.70%, to a risk of 2.79%. The Portfolio 6, composed by tomato and beef cattle activities, offer a minor level of risk when compared to other portfolios, 0.35%, to a monthly operational payback of 3.33%. The choice of the best portfolio is done when the user takes into account the level of risk which he or she is able to face. It was also possible to check that the activity diversification promotes the reduction of the non-systemic risk until a certain limit amount of agricultural activities in the portfolio. The Efficient Frontiers showed each combination of risk and payback that makes up the portfolio, further offering great resource allocations (land and capital).